Relationship Between Glycoprotein IIIa Platelet Receptor Gene Polymorphism and Coronary Artery Disease. (January 2015) - Verdoia, Monica; Cassetti, Ettore; Schaffer, Alon; Barbieri, Lucia; Giovine, Gabriella Di; Nardin, Matteo; Marino, Paolo; Sinigaglia, Fabiola; Luca, Giuseppe De
Glycoprotein IIb/IIIa (GP IIb/IIIa) is a key receptor for platelet aggregation and adhesion. We investigated whether a single-nucleotide polymorphism of GP IIIa subunit (Leu33Pro-PlA 1 /PlA 2 allele) is associated with the extent of coronary artery disease (CAD) in a consecutive cohort of 1518 patients undergoing coronary angiography. Significant CAD was defined as at least a stenosis >50% and severe CAD as left main disease and/or trivessel disease. Additionally, carotid intima–media thickness (cIMT) was evaluated in 339 patients. The PlA 2 allele was observed in 458 (30.2%) patients and associated with hypercholesterolemia ( P = .03). No difference was observed in the prevalence of CAD (72.6% vs 70.1%, P = .29; adjusted odds ratio, OR [95% confidence interval, CI] = 0.85 [0.67-1.08], P = .19) and severe CAD (27.5% vs 26.5%, adjusted OR [95% CI] = 0.93 [0.72-1.19], P = .55). Furthermore, Leu33Pro polymorphism did not affect cIMT and the prevalence of carotid plaques. Therefore, this polymorphism cannot be regarded as a risk factor for coronary or carotid atherosclerosis.